Socioeconomic factors and lifestyle affecting the variability of menstrual cycle characteristics in women from Central Poland - Nieczuja-Dwojacka, Joanna; Borowska, Beata; Janiszewska, Agata; Kozieł, Sławomir (Anthropological Review, 2019)
Regularity, length of the cycle and duration of menstrual flow are a reflection of women health. The purpose of the research was to assess the relationships between socioeconomic status, cycle length, duration of menses, regularity and dysmenorrhea. A survey was conducted among 896 healthy women from Łódź and Warsaw (Poland), aged 15.71–26.98. Women who were menarche at least 3 years ago were asked to complete the survey. Women were asked about cycle length (number of days), duration of menstrual flow, regularity of the cycle, dysmenorrhea, birth place, parental education level, attendance at physical education classes, participation in additional sports activities, self-assessment of stress levels at home and at school/university, and smoking. For data analysis, t-test, analysis of variance, and chi-square were used, and p<0.05 was considered to be statistically significant. There were no significant relationships between the mean cycle length, regularity and the environmental factors, except for differences in the average length of the menstrual cycle in women from Łódź who attend additional sports activities. Women who are more physically active are characterized by a shorter menstrual cycle. In terms of the length of the menstrual flow, daughters of better educated fathers were characterized by longer menses. In contrast, dysmenorrhea was associated with longer menstrual periods and longer menstrual bleeding, as well as with higher levels of stress, both at home and at school. Environmental factors affected the features of menstruation cycles in women from Central Poland.